Development and validation of a novel tool: The family resilience assessment scale for flood-affected families (FRAS-FAF) - Haleema Sadia; Boonjai Srisatidnarakul; Jen-Jiuan Liaw (Natural Hazards Research)
Family resilience is critical in coping with disasters such as floods, yet there is a lack of tools specifically designed to assess family resilience in flood-prone regions. This study aimed to develop and validate the Family Resilience Assessment Scale for Flood-Affected Families (FRAS-FAF), a culturally sensitive tool tailored to families impacted by recurrent flooding in Pakistan. A mixed-methods study design was employed in two phases. In Phase I, qualitative data were collected through in-depth interviews with heads of flood-affected families in the Nowshera district of Pakistan, revealing key themes related to family resilience. These insights informed the creation of 54 initial items for the FRAS-FAF. In Phase II, the psychometric properties of the tool were assessed using factor analysis with 400 participants, allocated for Exploratory Factor Analysis (EFA) 200 and the remaining 200 for Confirmatory Factor Analysis (CFA). The final version of the scale retained 52 items across five factors: Family Culture, Family Structure, Family Spirituality, Family Resources, and Environment. EFA and CFA confirmed a strong five-factor structure, with model fit indices demonstrating adequate construct validity (χ2 ​= ​1551/df ​= ​936, CFI ​= ​.91, TLI ​= ​.89, SRMR ​= ​.075, RMSEA ​= ​.057). Internal consistency was high for all factors, with Cronbach's alpha values ranging from .85 to .96. FRAS-FAF is a reliable and valid tool for assessing family resilience in flood-affected families. It provides a framework for practitioners and policymakers to identify areas of strength and vulnerability, informing the development of targeted interventions aimed at enhancing family resilience in flood-prone regions. The tool's culturally sensitive design ensures its relevance for flood-affected families in Pakistan and offers the potential for adaptation in other disaster-prone areas.